"Жіноче письмо" в історіографічному дискурсі України: до постановки проблеми - Андросова-Байда, Д. (Інститут історії України НАН України, 2008)
The article reviews the research potential of the phenomenon of women’s writing in historiographical science. Raises questions of the legitimize women- historian in the Ukrainian historiographical discourse, highlighting characters of the female scientific work. Key words: women's writing, a woman historian, scientific writing.